Cost analysis of psoriasis treatment modalities in Malaysian public hospitals - Azizam NA; Saperi S; Aniza Ismail; Norazirah MN; Zafar A; Azura MA; Tan, WC; Chan, LC; Tey, KE (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Psoriasis imposes a great economic burden as a result of higher expenditures for different interventions, diagnostic procedures, pharmaceuticals and loss of productivity. Less is known about the economic impact of psoriasis treatment in Asean region. The aim of this research was to calculate the costs associated with four psoriasis treatment modalities. A prospective cohort study was conducted in five hospitals involving 91 moderate to severe psoriasis patients. Costs were calculated from the societal perspective using the principle of Step Down and Activity Based Costing (ABC) within a six (6) months follow-up duration. The components of the costs borne by the provider were inpatient cost, cost of medication, laboratory investigation and radiology. Patient’s cost included out of pocket expenses, travelling cost and loss of productivity. Cost per patient per day was RM1,105.24 (inpatient) (US$315.94) and RM298.02 (outpatient) (US$85.19). Medication accounted for almost 90% (RM457,014.00) (US$130 638.45) of the total provider cost. Meanwhile, loss of productivity represented 84% (RM167,439.00) (US$47,862.80) of the total patient’s cost. Biologic treatment exhibited the highest cost which was RM342,377.00 (US$97,869.21), followed by systemic treatment (RM105,607.00) (US$30,187.99), topical treatment (RM38,280.00) (US$10,942.42) and topical phototherapy treatment (RM21,824.00) (US$6,238.44). Understanding the relationship between direct and indirect costs from both perspectives is important to accurately identify and evaluate effective treatment for psoriasis.